Nonlinear constitutive models of rock structural plane and their applications - Wenlin Feng; Shuangjian Niu; Chunsheng Qiao; Dujian Zou (Journal of Rock Mechanics and Geotechnical Engineering, 2024)
Structural planes play an important role in controlling the stability of rock engineering, and the influence of structural planes should be considered in the design and construction process of rock engineering. In this paper, mechanical properties, constitutive theory, and numerical application of structural plane are studied by a combination method of laboratory tests, theoretical derivation, and program development. The test results reveal the change laws of various mechanical parameters under different roughness and normal stress. At the pre-peak stage, a non-stationary model of shear stiffness is established, and three-dimensional empirical prediction models for initial shear stiffness and residual stage roughness are proposed. The nonlinear constitutive models are established based on elasto-plastic mechanics, and the algorithms of the models are developed based on the return mapping algorithm. According to a large number of statistical analysis results, empirical prediction models are proposed for model parameters expressed by structural plane characteristic parameters. Finally, the discrete element method (DEM) is chosen to embed the constitutive models for practical application. The running programs of the constitutive models have been compiled into the discrete element model library. The comparison results between the proposed model and the Mohr-Coulomb slip model show that the proposed model can better describe nonlinear changes at different stages, and the predicted shear strength, peak strain and shear stiffness are closer to the test results. The research results of the paper are conducive to the accurate evaluation of structural plane in rock engineering.